2010
DOI: 10.1192/pb.bp.108.024000
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic prescribing practice among child psychiatrists and community paediatricians

Abstract: Aims and methodAll child and adolescent psychiatrists and community paediatricians in the former Trent Region were surveyed about their antipsychotic prescribing practice during 1 year, including monitoring, and whether they would like consensus guidelines on prescribing and monitoring of antipsychotics in children and adolescents.ResultsThe majority (88%) of child psychiatrists and 33% of paediatricians had prescribed atypical antipsychotics, most commonly risperidone. Only two psychiatrists had prescribed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…It is noted that a growing number of antipsychotic prescriptions among children and adolescents are for 'off-label' use in the treatment of non-psychotic conditions such as conduct and behavioural disorders (Otasowie et al, 2010). Although accepted as commonplace in the general adult setting, the extent of off-label prescribing among children and adolescents in the UK is unknown (Baldwin and Kosky, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that a growing number of antipsychotic prescriptions among children and adolescents are for 'off-label' use in the treatment of non-psychotic conditions such as conduct and behavioural disorders (Otasowie et al, 2010). Although accepted as commonplace in the general adult setting, the extent of off-label prescribing among children and adolescents in the UK is unknown (Baldwin and Kosky, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade there has been substantial increase in the use of antipsychotic medication in children and adolescents (Vitiello et al, 2009). Studies in both UK (Clark, 2004, Otasowie et al, 2010) and US (Patel et al, 2005) show a switch from first line use of first generation antipsychotics (FGA) such as Haloperidol and Sulpiride to second generation antipsychotics (SGA) such as Olanzapine, Risperidone and Amisulpride. The recently completed baseline for the Prescribing Observatory for Mental Health‐UK study of antipsychotic medication in children and adolescents showed 90% of prescriptions were of SGAs (Prescribing Observatory for Mental Health, 2010).…”
Section: Background and Brief Literature Reviewmentioning
confidence: 99%
“…For a period SGAs became the first line choice due to presumed better tolerability and improved likelihood of better concordance and outcome (Otasowie et al, 2010; Patel et al, 2005) This is now being increasingly questioned (Varley & McClellan 2009; Lewis & Lieberman, 2008). Large trials in both the UK and US (i.e.…”
Section: Background and Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…P Background: Psychotropic medication is increasingly used in children to treat psychiatric symptoms or illnessess [1] and behaviours associated with autistic spectrum disorders [2]. Child and adolescent psychiatrists report that stimulants or antipsychotics, namely the atypical antipsychotics, are the medicines they use most frequently in this population [3].…”
mentioning
confidence: 99%